Bioactivity of Antibacterial Compounds Produced by Endophytic Actinomycetes from Neesia altissima - Pratiwi, Rina Hidayati; Hanafi, Muhammad; Artanti, Nina; Pratiwi, Rosa Dewi (Journal of Tropical Life Science, 2018)
Identification of alternate bioactive compounds isolated from microbial endophytes from plants may lead to better solution against antibiotic resistance. Main objective of this research is to determine the bioactivity of antibacterial compounds produced by endophytic actinomycetes, which was isolated from stem bark of Neesia altissima Bl. at Halimun Salak Mount. Detection of bioactive compounds was assayed using Thin Layer Chromatography (TLC) by employing bioautography. Bioactivity was assayed using crude extract against five microorganisms using agar diffusion methods. Tetracycline was used as a positive control. The result of antibacterial activity from endophytic actinomycetes isolate revealed that the bioactive compounds were effective in inhibiting the growth of bacteria Bacillus cereus (1.25 mm), Salmonella typhimurium (5.75 mm), and Shigella flexneri (4.37 mm). Bioactivity of ethyl acetate extract from bioactive compounds of endophytic actinomycetes has an antibacterial activity against bacteria Bacillus cereus (13.00 mm) and Staphylococcus aureus (15.90 mm), at a concentration of 250,000 ppm. Each of TLC fraction was able to inhibit growth of B. cereus at a minimum concentration of 10,000 ppm. In conclusion, the bioactive compounds produced by endophytic actinomycetes can have inhibitory effect towards B. cereus. The category of that compounds are narrow spectrum. The bioactive compound isolated from endophytic actinomycetes may have other implications such as anticancer, antifungal, and antioxidant.